2010
DOI: 10.1164/rccm.200906-0826oc
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Sphingosine 1-Phosphate Signaling as an Alveolar Cell Survival Strategy in Emphysema

Abstract: Rationale: Vascular endothelial growth factor receptor (VEGFR) inhibition increases ceramides in lung structural cells of the alveolus, initiating apoptosis and alveolar destruction morphologically resembling emphysema. The effects of increased endogenous ceramides could be offset by sphingosine 1-phosphate (S1P), a prosurvival by-product of ceramide metabolism. Objectives: The aims of our work were to investigate the sphingosine-S1P-S1P receptor axis in the VEGFR inhibition model of emphysema and to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 47 publications
1
56
0
Order By: Relevance
“…For example, induction of apoptosis by imatinib in a human cell line (K562) increased the CER/S1P ratio, while sphingosine addition increased S1P and reduced this ratio (Baran et al, 2007). In a lung cell culture, induction of emphysema by angiogenesis inhibition, the CER/S1P ratio obtained was 1.1, while the addition of S1P reduced emphysema and the ratio CER/S1P to 0.7 (Diab et al, 2010). Similarly, in the present study, the S1P/CER ratio was higher in healthy than atretic antral follicles.…”
Section: Discussionmentioning
confidence: 99%
“…For example, induction of apoptosis by imatinib in a human cell line (K562) increased the CER/S1P ratio, while sphingosine addition increased S1P and reduced this ratio (Baran et al, 2007). In a lung cell culture, induction of emphysema by angiogenesis inhibition, the CER/S1P ratio obtained was 1.1, while the addition of S1P reduced emphysema and the ratio CER/S1P to 0.7 (Diab et al, 2010). Similarly, in the present study, the S1P/CER ratio was higher in healthy than atretic antral follicles.…”
Section: Discussionmentioning
confidence: 99%
“…The incomplete recovery of histology, sphingolipid levels and lung function after D-sphingosine treatment and the absence of a significant difference in these parameters between hyperoxic mice with and without D-sphingosine might be due to dose and/or timing of the supplementation, or might have been missed due to relatively small numbers of observations. Our D-sphingosine dose was based on a study by DIAB et al [35] who showed that adult mice injected with D-sphingosine at 20 mg per mouse for five consecutive days had significantly increased sphingosine-1-phosphate (a pro-survival sphingolipid) levels in homogenised lung tissue at day 5 after the start of administration. The administration of D-sphingosine in our model started after hyperoxia exposure and lasted for 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ceramide species identification and quantification, as well as sphingosine-1 phosphate content, were determined by liquid chromatography/tandem mass spectrometry (12). Sphingolipid levels were normalized by lipid phosphorus (12).…”
Section: Sphingolipid Measurementmentioning
confidence: 99%